Physical, Static, and Kinetic Analysis of the Electrochemical Deposition Process for the Recovery of Heavy Metal from Industrial Wastewater - Ridha Hamdi; Amani Rached; Amal L. Al–Otaibi; Imen Massoudi; Shouq Alkorbi; Amor Saidi Ben Ali (Scientifica)
Through the electrodeposition technique, toxic metals in wastewater can be removed and deposited on a chosen substrate with excellent selectivity. In this work, we use this technique to extract lead cations from simulated wastewater by using fluorine-doped tin oxide (FTO) substrate at various temperatures. In situ tracking of lead nucleation at advanced stages has been achieved by chronoamperometry. According to the experimental results, the theoretical models developed to study the kinetic growth of lead deposits in 2D and 3D are in good agreement. Nucleation rate and growth rate constants, for example, were found to be strongly influenced by temperature. Cottrell’s equation is used to calculate the diffusion coefficient. X-ray diffraction, scanning electron microscopy, and energy-dispersiveX-ray techniques were used to investigate and characterize the lead deposits. The reported results could provide insight into the optimization of electrodeposition processes for heavy metal recovery from wastewater and electronic wastes.